Reflective Teaching Practice among EFL Teachers in Special Region of Yogyakarta - Zukrina Kholis; Suwarsih Madya (Makassar State University, 2021)
Abstract. Implementing reflective teaching enables teachers to enhance their professional development. Considering this role, this study aimed to find out how much EFL teachers have practiced reflective teaching and its relation with gender, length of teaching, and brain hemisphere dominance. This is a quantitative study which followed the correlational approach. The data collection was obtained by distributing the instruments of this study namely: the questionnaire and the quiz. The data in this study were collected from the EFL public Senior High School teachers in the Special Region of Yogyakarta. The reported result reveals that the EFL teachers are mostly in the level of pedagogical reflection (33.01%) and all of the chosen variable predictors seemed to have no influence in determining the teachers’ reflection practice level. Keywords: EFL teacher, reflective teaching, gender, teaching experience, brain hemisphere dominance